(untitled) (Jurnal Kemanusiaan, 2017)
ABSTRACT Most studies in the West indicate that transsexual groups are free to take advantage of community infrastructure surrounding them in order to construct and strengthen their identitiy and transsexual way of life. Transsexual phenomenon has also become more evident in Malaysia, especially among male students in the higher education institutions. The objective of this study is to examine the role of community infrastructure surrounding Malaysian higher education institutions in constructing and strengthening the identity of this group. A three year study (2006- 2009) was conducted on 60 male transsexual students in two public higher education institutions, namely Universiti Sains Malaysia (USM) and Universiti Utara Malaysia (UUM). Snowball sampling method was facilitated in choosing 30 respondents from each universities. Qualitative methods were used in the collection and interpretation of data, which include open endedÂ questionnaire survey, in-depth and repeated interviews, face-to-face discussion and chatting via internet, diary writing and also participation observation. This study uncovers that community infrastructure surrounding the universities â€“ such as cafe cyber, shopping complexes, pharmacies, bookstores and premises selling newspapers and magazines, beauty salons and spas, and also recreational parks â€“ are used widely by this group in order to construct and strengthen their transgender identity. This study contributes to the understanding and knowledge on transsexual phenomenon in Malaysia which is now spreading and is showing the similiar trend with those of the West, in which a large proportion of this has been contributed by the community structure that supported their needs. ABSTRAK Kebanyakan kajian di Barat menunjukkan golongan transeksual bebas menggunakan infrastruktur komuniti di sekitar tempat tinggal mereka untuk membina dan mengukuhkan gaya hidup transeksual. Fenomena transeksualisme juga semakin ketara di Malaysia, khasnya di kalangan pelajar institusi pengajian tinggi. Objektif kajian ini adalah untuk mengkaji peranan infrastruktur komuniti di dalam dan sekitar institusi pengajian tinggi di Malaysia dan cara ianya membina dan mengukuhkan identiti golongan ini. Kajian tiga tahun (2006-2009) telah dijalankan ke atas 60 pelajar lelaki transeksual di dua buah institusi pengajian tinggi awam iaitu Universiti Sains Malaysia (USM) dan Universiti Utara Malaysia (UUM). Metod persampelan snowball telah digunakan bagi mendapatkan 30 orang responden daripada setiap universiti dikaji. Pengumpulan data dilakukan menggunakan kaedah kualitatif yang melibatkan soalselidik terbuka, temubual mendalam dan berulangan, komunikasi secara bersemuka dan melalui ruangan sembang di internet, penulisan diari, dan pemerhatian ikut serta. Kajian ini mendapati infrastruktur komuniti di dalam dan sekitar kawasan universiti - seperti kafe siber, pusat membeli belah, farmasi, premispremis menjual majalah dan surat khabar, spa dan salun serta kawasan rekreasi - telah digunakan dengan meluas oleh golongan ini untuk membina dan mengukuhkan identiti mereka sebagai transeksual. Implikasi kajian ini adalah menyumbangkan kepada pengetahuan dan pemahaman tentang bagaimana fenomena transeksual di Malaysia semakin menular dan mempunyai trend yang sama dengan keadaan di Barat, yang mana sebahagian besarnya disumbangkan oleh infrastruktur komuniti yang menyokong keperluan mereka.